An Entanglement between Nature and the Supernatural: the Early Second Millennium BCE Ceremonial Complex of Hirbemerdon Tepe in the Upper Tigris Region - Laneri , Nicola (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
In order to understand the social organization of ancient communities inhabiting a specific settlement, archaeologists analyze the material culture discovered during a site’s extensive archaeological excavation. These data can be linked to the broader regional environment through the use of archaeobotanical, archaeozoological, geoarchaeological, and artifactual analyses as well as survey of the region surrounding the site. This research process can also establish an epistemological trajectory that attempts to find patterns of connections between human beings and their environment, in what Ingold (2000: 5) defines as ‘the task of making a living’. This approach focuses on the economic dimension of the relationship between human beings and nature, but it also emphasizes the importance of the landscape and its attributes in transmitting cultural knowledge among the members of a community.